PENGARUH PARTISIPASI ANGGARAN, SELF-EFFICACY, SISTEM PENGUKURAN KINERJA, DAN SISTEM REWARD PADA KINERJA MANAJERIAL - Negara, I Gede Jemika; ., Gayatri (E-Jurnal Akuntansi, 2017)
The purpose of this research is to determine any factors that may affect the managerial performance of department head of star-rated hotels in Denpasar. The background of this research is the decrease of the average occupancy rate of star rated hotel rooms in Denpasar City. This research located at 29 star-rated hotels in Denpasar and the respondents are 35 of department heads that have been choosen by purposive sampling method. Data was collected by using questionnaire and then analyzed by multiple regression. This study found that budgetary participation, self-efficacy, and reward system have positive impact on managerial performance, and performance measurement system has no impact on managerial performance. Budgetary participation could increase goal-commitment that have implication on managerial motivation to improve performance. Furthermore, the heads of departments with high self-efficacy have a strong belief in achieving goals that tend to set higher targets and produce high performance. The reward system can align personal goals with corporate objectives so that department heads will act in the company's best interest to achieve high performance. Meanwhile, performance measurement systems has no effect on managerial performance because of department heads are more interested in rewards given in the form of service charges that do not have a direct relationship to the performance measures specified in the performance measurement system in some departments. Keywords : managerial performance, budgetary participation, self-efficacy, performance measurement system, reward system